Structural insights into the agonist selectivity of the adenosine A3 receptor - Hidetaka S. Oshima; Akiko Ogawa; Fumiya K. Sano; Hiroaki Akasaka; Tomoyoshi Kawakami; Aika Iwama; Hiroyuki H. Okamoto; Chisae Nagiri; Fan-Yan Wei; Wataru Shihoya; Osamu Nureki (Nature Communications)
Abstract Adenosine receptors play pivotal roles in physiological processes. Adenosine A3 receptor (A3R), the most recently identified adenosine receptor, is expressed in various tissues, exhibiting important roles in neuron, heart, and immune cells, and is often overexpressed in tumors, highlighting the therapeutic potential of A3R-selective agents. Recently, we identified RNA-derived N 6-methyladenosine (m6A) as an endogenous agonist for A3R, suggesting the relationship between RNA-derived modified adenosine and A3R. Despite extensive studies on the other adenosine receptors, the selectivity mechanism of A3R, especially for A3R-selective agonists such as m6A and namodenoson, remained elusive. Here, we identify tRNA-derived N 6-isopentenyl adenosine (i6A) as an A3R-selective ligand via screening of modified nucleosides against the adenosine receptors. Like m6A, i6A is found in the human body and may be an endogenous A3R ligand. Our cryo-EM analyses elucidate the A3R-Gi complexes bound to adenosine, 5’-N-ethylcarboxamidoadenosine (NECA), m6A, i6A, and namodenoson at overall resolutions of 3.27 Å (adenosine), 2.86 Å (NECA), 3.19 Å (m6A), 3.28 Å (i6A), and 3.20 Å (namodenoson), suggesting the selectivity and activation mechanism of A3R. We further conduct structure-guided engineering of m6A-insensitive A3R, which may aid future research targeting m6A and A3R, providing a molecular basis for future drug discovery.